The Contribution of Local Tribun Newspaper to Development Progress In Bone District - Andi Asdar; Hasrullah Hasrullah; Andi Alimuddin Unde; Muliadi Mau (Peneliti.net, 2023)
This type of qualitative research through a phenomenological approach, while the results of the study show that the mass media, especially the Bone Local tribune newspaper, plays a very important role in informing and socialising various development programs, including in preparing data, information and conditions in the field so that they become material for consideration in building a concept of development planning Mass media has a huge influence on various dimensions, both in the economic, political, legal, social, agricultural, educational, health and so on. The mass media is the main funnel of change in society or the state towards improving people's lives in various dimensions. However, this also means that the mass media has two principle functional roles, namely positive and negative.